2005
DOI: 10.1002/mrd.20378
|View full text |Cite
|
Sign up to set email alerts
|

Isolation, culture, and characterization of embryonic cell lines from vitrified sheep blastocysts

Abstract: This study was conducted to isolate, to culture, and to characterize embryonic cell lines from in vitro produced vitrified sheep blastocysts. Embryos were produced and vitrified at the expanded blastocyst stage. Ten inner cell masses arising from day 6-7 blastocysts were isolated by immunosurgery, disaggregated, and cultured onto mitomocin-C-inactivated mouse STO fibroblasts (MIF). After 5 or 6 days of culture the primary cell colonies were disaggregated, seeded in a new MIF, and cultured for 3 or 4 days to fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
46
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(51 citation statements)
references
References 49 publications
5
46
0
Order By: Relevance
“…Morphologically, ICM-derived undifferentiated primary colonies were densely packed with clear border on all the feeders and synthetic matrices while differentiated colonies showed cystic EBs at their periphery. Our findings were similar to Verma et al (11) (24), however in pig (25), dog (26) and sheep (27) ESCs express SSEA-1. Contradictory reports are available in bovines on the presence of SSEA-1 in ESCs, some studies showed its presence (14, 28) while others did not (29).…”
Section: Discussionsupporting
confidence: 92%
“…Morphologically, ICM-derived undifferentiated primary colonies were densely packed with clear border on all the feeders and synthetic matrices while differentiated colonies showed cystic EBs at their periphery. Our findings were similar to Verma et al (11) (24), however in pig (25), dog (26) and sheep (27) ESCs express SSEA-1. Contradictory reports are available in bovines on the presence of SSEA-1 in ESCs, some studies showed its presence (14, 28) while others did not (29).…”
Section: Discussionsupporting
confidence: 92%
“…Thus, it would be desirable, for economic reasons, to use embryos produced from in vitro matured and fertilized oocytes. However, up to now, only a few ES-like lines have been established in farm animals from in vitro produced material [33][34][35]. The first attempt to use in vitro blastocysts in the pig was described by Miyoshi et al [36].…”
Section: The Age and The Source Of Embryosmentioning
confidence: 99%
“…The use of frozen-thawed (FT) and ICSI produced blastocysts for production of porcine stem cell lines has yet to be reported in spite of the fact that the above techniques have been used (with and without success) for production ES cell lines in other species (horse FT [10]; sheep FT [35]; primate ICSI [43]; human ICSI [44]; human FT [45]). Another possibility is to establish ES cell lines from blastocysts produced by nuclear transfer.…”
Section: The Age and The Source Of Embryosmentioning
confidence: 99%
“…SSEA1, SSEA4, and tumor rejection antigens (TRA-1-60 and TRA-1-81) are regarded as markers of human (Carpenter et al, 2003;Henderson et al, 2002), primate (Liu et al, 2004;Thomson et al, 1995), and bovine ESCs (Dattena et al, 2006;Mitalipova et al, 2001;Saito et al, 2002). The FOXD3 forkhead transcription factor is required for maintaining pluripotent cells in early mouse embryo and for establishment of murine ESC lines (Liu and Labosky, 2008), whereas CD90 has been used as human ESC marker (Fang et al, 2005) as well as a marker for spermatogonial and mesenchymal stem cells (Kobayashi et al, 2009).…”
Section: Discussionmentioning
confidence: 99%